Purchase intention on Bukalapak: Role of risk, convenience, and benefits - Ahyani, Ahyani; Solihin, Dede (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine how perceived risk, perceived convenience, and perceived benefits influence users’ purchase intention on Bukalapak, one of Indonesia’s leading e-commerce platforms. Methodology: The study was conducted using a quantitative method with a survey distributed to 100 active Bukalapak users across various cities in Indonesia. Data were collected using a structured questionnaire and analyzed using SmartPLS 4.0 software to test the relationships between the constructs based on the extended Technology Acceptance Model (TAM). Results: The results show that perceived convenience and perceived benefits have a significant positive impact on purchase intention, while perceived risk has a significant negative impact. This indicates that users are more likely to make purchases on Bukalapak when they perceive the platform as easy to use and beneficial, and less likely when they feel uncertain or insecure. Conclusions: The study concludes that increasing convenience and delivering tangible benefits can strengthen purchase intention, while managing and reducing user risk perceptions is crucial to improving user confidence. Limitations: The study is limited to Bukalapak users and uses a relatively small sample size (n = 100), which may not fully represent the broader population of e-commerce users in Indonesia. Contribution: This study contributes to the understanding of consumer behavior in Indonesian e-commerce by validating the extended TAM in the context of Bukalapak. It provides insights for e-commerce managers, marketers, and platform developers to design better strategies that enhance user trust and buying interest.